Key ideas in contract law - McBride, Nicholas J. (Key ideas in law, 2017)
[This book] introduces the reader to a number of ideas and issues that underlie the English law of contract ... Taking as its starting point the role contract law plays in helping markets to operate, [the] author ... explains how contract law regulates the commercial risks people take, while at the same time placing limits on what may be bought and sold, and ensuring that contractual powers are not unacceptably abused. A final chapter discusses how contract law can be used to make gifts of binding promises to other people.